Suspicion and surveillance - BORRELLI, LISA MARIE; HEINDLMAIER, ANITA; MANTU, SANDRA; PFIRTER, LUCA (Critical social policy, 2024)
In this article we focus on contemporary processes of social differentiation and exclusion at the intersection of migration policy and welfare governance. The keyword pair looks at bureaucratic practices, their justifications, and their consequences for non-citizen subjects’ paths and moves on to theorise about the permeation of these practices into society. We discuss the effects of the suspicion-surveillance nexus on the observed body and mind and how they operate in support of increasingly intrusive practices. Rather than debating the legality of such practices and the inequalities and power relations they imply, we focus on the possibilities of control as discourses become technologised.